1965
DOI: 10.1037/h0021632
|View full text |Cite
|
Sign up to set email alerts
|

Effect of strength of drive determined by a new technique for appetitive classical conditioning of rats.

Abstract: A new method of appetitive classical conditioning has the great economy of using laboratory rats and tongue-licking, a short-latency response. Tests for effect of drive on learning were carried down to the theoretically crucial level of zero relevant drive, with adequate exposure to the goal substance. When rats were classically conditioned under 4 levels of thirst drive, high drive Ss learned better than moderate drive ones, who learned better than satiated and supersatiated Ss which showed no appreciable lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
24
1

Year Published

1967
1967
2004
2004

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(27 citation statements)
references
References 6 publications
(3 reference statements)
2
24
1
Order By: Relevance
“…Hulse has also drawn attention to respondent properties of the tongue-lick and several Es (see, e.g., DeBold, Miller, & Jensen, 1965) have indeed found it amenable to classical conditioning. That rats have exhibited stable licking to low-ratio intermittent schedules (Hulse, Snyder, & Bacon, 1960) would be expected-a single water reinforcement may e lic ita burst of eight or more licks, Demonstration of the tongue-lick as a useful "free" operant would therefore entail stable performance on an intermittent schedule the ratio of which exceeds the number of responses in a respondent burst.…”
mentioning
confidence: 99%
“…Hulse has also drawn attention to respondent properties of the tongue-lick and several Es (see, e.g., DeBold, Miller, & Jensen, 1965) have indeed found it amenable to classical conditioning. That rats have exhibited stable licking to low-ratio intermittent schedules (Hulse, Snyder, & Bacon, 1960) would be expected-a single water reinforcement may e lic ita burst of eight or more licks, Demonstration of the tongue-lick as a useful "free" operant would therefore entail stable performance on an intermittent schedule the ratio of which exceeds the number of responses in a respondent burst.…”
mentioning
confidence: 99%
“…As have other investigators , however , they found that both the mean and modal lick rates for rats were 6·7 licks/sec. Further evidence for the highly invariant , elicited, reflexive nature of licking in the rat has been provided by Snyder & Hulse (1961), DeBold , Miller, & Jensen (1965), Boice & Denny (1965), Hulse (1966), and Schaeffer & Smith (1966). These studies, in addition to revealing that the lick response fatigued , could be classically conditioned , and , once init iated, was reflexive, all reported that lick rate was essentially constant.…”
mentioning
confidence: 86%
“…In the techniques of DeBold, Miller, and Jensen (1965) it is necessary to drill through the nasal sinuses, which can lead to severe hemorrhaging. The method of Gross, Trapold, and Hyde (1968) is simpler, but still requires drilling between the incisors, as well as fitting a metal hypodermic tube tc the shape of each experimental animal's muzzle.…”
mentioning
confidence: 99%